The Potential Role of Uterine Retroversion in Pelvic Pain Symptoms and Caesarean Delivery - Meral Tuğba Acar Çimşir; Muhammet Serhat Yıldız (Acta Medica Alanya)
Aim: Uterin Retroversion is a common status in the women population and assumed to be related with pelvic pain symptoms. The aim of this study is to investigate whether uterine retroversion is associated with pelvic pain symptoms and is a reason for cesarean delivery.Method: One hundred thirty-three premenopausal women admitted in a Tertiary Education and Research Hospital, Department of Gynecology unit for pregestational counseling were evaluated for pelvic pain symptoms with a self-administrated questionnaire. Uterine position was assessed by pelvic examination and transvaginal ultrasound. Sixty-one women had a retroverted uterus (group1), and seventy-two had an anteverted or intermediate uterus (group2). Dyspareunia, dysmenorrhea, weight, Body Mass Index (BMI), cyclic pain, ovulation pain, premenstrual pain and mode of delivery were compared between the Retroverted group and the Anteverted or intermediate group. After successful conception and pregnancy survey, mode of delivery was also compared.Results: Dyspareunia, dysmenorrhea, weight, BMI, cyclic pain, ovulation pain, premenstrual pain, patients’ sexual activities restrictment due to dyspareunia, patients medical treatment requirement for dysmenorrhea, and mode of delivery was statistically significant between two groups. (p<0.05). However, PMS (premenstrual syndrome), height, gravid and parity were similar (p>0.05).Conclusion: Uterine retroversion is associated with a higher prevalence of cesarean rate, pelvic pain and visual analogue scale for dyspareunia and dysmenorrhea in a population of unselected women.